Reexamining Stock Valuation and Inflation: The Implications Of Analysts' Earnings Forecasts - Sharpe, Steven A. (The Review of Economics and Statistics, 2002)
This paper examines the effect of inflation on stock valuations and expected long-run returns. Ex ante estimates of expected long-run returns are constructed by incorporating analysts' earnings forecasts into a variant of the Campbell-Shiller dividend-price ratio model. The negative relation between equity valuations and expected inflation is found to be the result of two effects: a rise in expected inflation coincides with both lower expected real earnings growth and higher required real returns. The earnings channel mostly reflects a negative relation between expected long-term earnings growth and expected inflation. The effect of expected inflation on required (long-run) real stock returns is also substantial. An increase of one percentage point in expected inflation is estimated to raise required real stock returns about one percentage point, which on average would imply a 20% decline in stock prices. But the inflation factor in expected real stock returns is also in long-term Treasury yields; consequently, expected inflation has little effect on the long-run equity premium.